School space selection preferences: Architectural perspective toward formal school - Kurnia Widiastuti; Mohamad Joko Susilo; Hanifah Sausan Nurfinaputri (Institute of Advanced Engineering and Science, 2021)
School space plays an essential role in creating a pleasurable learning atmosphere. The tendency of everyone to choose a school space also varies. By knowing this trend pattern, schools can be designed to improve student learning effectiveness. The purpose of this study was to find out which school spaces students choose to study, what kind of room criteria are needed, and distribution patterns of students' preference choices. This research used both the qualitative exploratory and quantitative methods using an open-ended question questionnaire for data collection. Data analysis techniques used qualitative analysis methods consisting of open coding, axial coding, and selective coding. The results showed that the library, mosque, and multimedia laboratory were the most preferred space for students to study at school. Some factors that influence the selection include thermal comfort, completeness of supporting facilities, and acoustic comfort.